Estatinas, drogas de amplio espectro de acción y beneficios - Arocha-Rodulfo, Ildefonzo (Revista Hospital Clínico Universidad de Chile, 2019)
Prevention and treatment of dyslipidemia should therefore be considered as an integral partof individual cardiovascular prevention interventions, which should be addressed primarily tothose at higher risk who will benefit most. Statins are the most commonly used options forthe pharmacologic treatment of dyslipidemia. In recent decades, numerous clinical trials havedemonstrated the efficacy of these drugs to reduce cardiovascular mortality and major non-fatalatherothrombotic events in heterogeneous populations through both primary and secondaryprevention. This group of drugs is part of the recommendations of both US and Europeanguidelines, and should be prescribed to all patients who have already had a cardiovascularevent and have no specific contraindication. However, a large percentage of patients thatwould benefit from a statin treatment do not receive them, have been prescribed a low doseor for a limited time.